COVID-19 and open science: analysis of evidence and trends to delivery and share information - Juan Miguel Palma (14077800) (2023)
This paper was given by Juan Miguel Palma Peña, National Autonomous University of Mexico (UNAM); Humanities Coordination  The current situation of the SARS-CoV-2 virus pandemic responsible for Covid-19 highlights the development and implementation of multiple theoretical and empirical actions of an informative nature in which delivery and sharing data and scholarly outputs are in the focus of global attention. The opening of the research outputs is articulated so that the FAIR principles of location, accessibility, interoperability and reuse allow informational resources financed with public funds to be delivery and shared for the resolution of the current social phenomenon and to give continuity to educational and cultural activities political, scholarly, among others. The health crisis and the sharing of advances and research outputs in open access on various platforms crystallize the transition to open science, and a paradigm shift is articulated in which science is literally by and for society. This document is made based on the exploratory analysis of literature whose content is about open access, open science and Covid-19. After the analysis of the information, the interpretation and recommendations on the subject of study are made from the perspective of the library field and information studies. The aim of this document is to address the paradigm shift posed by open access and the transition to open research; as well as analyze the trends that the phenomenon of covid-19 manifests to delivery, share, exchange, make transparent and formalize the opening of research for the benefit of societies. The organization of this document consists of two sections, and they are the following: first, the evidence of open access, open science and covid-19 is analyzed based on data and actions of organizations and educational and research institutions to share information; second, the main trends for opening and sharing information are studied, such as open data, preprints and the formalization of this action.